2004
DOI: 10.1080/02813430410005676
|View full text |Cite
|
Sign up to set email alerts
|

Changes in urinary incontinence and quality of life after four years A population-based study of women aged 22–50 years

Abstract: At 4-year follow-up the type of UI is fairly stable in women below 50 years of age. The QoL decreases in five dimensions, but the clinical relevance of this might be questioned. Most women with UI had not sought professional help.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
38
0
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 20 publications
3
38
0
4
Order By: Relevance
“…McGrother et al 10 reported a 1-year incontinence incidence of 8% among female patients aged 40 to 59 years registered with 108 general practices. Two population-based studies 11,12 of women younger than age 60 years reported mean annual incidences ranging from 4% to 5%. Also, similar to our observation of a 1.8% average 1-year incidence of leaking at least once per week, Moller et al 13 Several limitations of this study should be considered.…”
Section: Commentmentioning
confidence: 99%
“…McGrother et al 10 reported a 1-year incontinence incidence of 8% among female patients aged 40 to 59 years registered with 108 general practices. Two population-based studies 11,12 of women younger than age 60 years reported mean annual incidences ranging from 4% to 5%. Also, similar to our observation of a 1.8% average 1-year incidence of leaking at least once per week, Moller et al 13 Several limitations of this study should be considered.…”
Section: Commentmentioning
confidence: 99%
“…16 Annual rates of UI incidence vary from 1% to 11% and of UI remission from 5% to 11%. [17][18][19][20][21][22][23][24] Most studies assessing the causes of UI are cross-sectional and therefore cannot assess UI as a dynamic condition. Moreover, the few longitudinal studies have had relatively limited follow-ups (2-5 years) or no interval evaluation of the UI evolution during the study period.…”
Section: Introductionmentioning
confidence: 99%
“…Установлено, что частота недержания мочи у женщин в менопаузе варьирует от 8 до 27% в зависимости от по-пуляции [8,9]. С. McGrother и соавт.…”
Section: ключевые слова: гиперактивный мочевой пузырь толщина стенкиunclassified